Improving Poetry Writing Skills Through the Problem-Based Learning Model in Grade X Students of SMA Negeri 5 Ambon - Seipattiseun, Alfian Heny; Somelok, Grace; Sapulette, Viona (Universitas Pattimura, 2024)
Education is a crucial determinant for the advancement of human existence, particularly in cultural and formal contexts. Formal education is an educational institution that enhances the quality of the teaching and learning process. In this context, poetry entails the composition of literary works characterized by succinct, rich, and aesthetically pleasing language, employing innovative phrasing, tangible expressions, artistic components, and human emotions articulated through rhythmic and emotive language. Consequently, an innovative learning strategy is required to enhance students' writing skills, namely through the implementation of the Problem Based Learning (PBL) model. This study aims to enhance poetry writing skills through the Problem Based Learning paradigm among class X students at SMA Negeri 5 Ambon. This research employs classroom action methodology